Targeting L-Proline Uptake as New Strategy for Anti-chagas Drug Development - Fargnoli, Lucía; Panozzo-Zénere, Esteban A.; Pagura, Lucas; Barisón, María Julia; Cricco, Julia A.; Silber, Ariel M.; Labadie, Guillermo R. (Frontiers in Chemistry, 2020)
L-Proline is an important amino acid for the pathogenic protists belonging to Trypanosoma and Leishmania genera. In Trypanosoma cruzi, the etiological agent of Chagas disease, this amino acid is involved in fundamental biological processes such as ATP production, differentiation of the insect and intracellular stages, the host cell infection and the resistance to a variety of stresses. In this study, we explore the L-Proline uptake as a chemotherapeutic target for T. cruzi. Novel inhibitors have been proposed containing the amino acid with a linker and a variable region able to block the transporter. A series of sixteen 1,2,3-triazolyl-proline derivatives have been prepared for in vitro screening against T. cruzi epimastigotes and proline uptake assays. We successfully obtained inhibitors that interfere with the amino acid internalization, which validated our design targeting the metabolite's transport. The presented structures are one of few examples of amino acid transporter inhibitors. The unprecedent application of this strategy on the development of new chemotherapy against Chagas disease, opens a new horizon on antiparasitic drug development against parasitic diseases and other pathologies.